Algunos aspectos del Caracol Africano “Achatina fúlica” y su prevalencia en la salud Pública en la Ciudad de Villavicencio (Colombia Suramérica) (2023)
Introduction: African snail is one of the 100 most important pests of invertebrates worldwide; a mollusk host of parasites that cause serious diseases to humans and domestic animals, so it represents a risk to biodiversity and public health.